2008
DOI: 10.1353/tech.0.0144
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Transnational History of Technology: Meanings, Promises, Pitfalls

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…The great majority of CI studies, however, address (sub)national cases. There is a need for transnational analysis in CI studies, which is about questioning and examining rather than presupposing relations between local, national and international developments (Van der Vleuten, 2008). Examining a case of transnational infrastructure vulnerability, we found that the 'international by nature' argument is not beyond dispute.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The great majority of CI studies, however, address (sub)national cases. There is a need for transnational analysis in CI studies, which is about questioning and examining rather than presupposing relations between local, national and international developments (Van der Vleuten, 2008). Examining a case of transnational infrastructure vulnerability, we found that the 'international by nature' argument is not beyond dispute.…”
Section: Discussionmentioning
confidence: 80%
“…To achieve this, we draw on recent work inspired by a transnational turn in technological history (Misa and Schot, 2005;Van der Vleuten, 2008) and infrastructure history in particular (e.g. Kaijser, 2005, 2006).…”
Section: Article In Pressmentioning
confidence: 99%
“…For an early discussion of the scope and the historiographical perspective of the group, see Misa and Schot (). See, also,Van der Vleuten and Kaijser (), Schot () and Van der Vleuten ().…”
mentioning
confidence: 99%
“…Among the various publications stemming from the Tensions of Europe network, the Making Europe book series (Palgrave Macmillan) is a groundbreaking work and an ambitious summary of research stemming from its first 15 years of existence. Other publications include Misa and Schot (); Schot (); Van der Vleuten (); Van der Vleuten and Kaijser ().…”
mentioning
confidence: 99%